2001
DOI: 10.1016/s1074-7613(01)00221-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of β2 Integrin Receptor and Syk Kinase Signaling in Monocytes by the Src Family Kinase Fgr

Abstract: While beta 2 integrin ligand-receptor recognition interactions are well characterized, less is known about how these events trigger signal transduction cascades to regulate the transition from tethering to firm adhesion, spreading, and transendothelial migration. We have identified critical positive and negative regulatory components of this cascade in monocytes. Whereas the Syk tyrosine kinase is essential for beta 2 integrin signaling and cell spreading, the Src family kinase Fgr is a negative regulator of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 52 publications
5
62
0
1
Order By: Relevance
“…5A). As described previously, the Fgr SH2 domain selects only the phosphopeptide containing both pTyr-342 and pTyr-346 in this same assay (9). We have found that the Lck SH2 domain exhibits the same binding specificity as the Fgr SH2 domain (data not shown).…”
Section: The P85 Regulatory Subunit Of Pi3k Interacts With Syk In Asupporting
confidence: 73%
See 2 more Smart Citations
“…5A). As described previously, the Fgr SH2 domain selects only the phosphopeptide containing both pTyr-342 and pTyr-346 in this same assay (9). We have found that the Lck SH2 domain exhibits the same binding specificity as the Fgr SH2 domain (data not shown).…”
Section: The P85 Regulatory Subunit Of Pi3k Interacts With Syk In Asupporting
confidence: 73%
“…Syk mediates signaling by interacting with these receptors via its tandem SH2 domains and functioning both as a catalyst for protein phosphorylation and as an adaptor for the formation of protein complexes. Sites of tyrosine phosphorylation within the linker B region at residues 317, 342, and 346 have been identified as docking sites for the SH2 domain-containing proteins c-Cbl, phospholipase C-␥, Fgr, and Vav (4,5,(7)(8)(9)(10). Other proteins with SH2 domains that have been reported to interact with Syk include PI3K, Lck, Lyn, CrkL, Grb2, Gab2, SHP1, and SHP2 (26, 32, 34 -38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction between Syk and TLR4 seen in neutrophils at baseline and upon LPS stimulation may be direct or indirect. Previously Syk has been shown to associate with CD18 and the Fc␥ receptor, both of which interact with TLR4 upon LPS stimulation in macrophages, which suggests an indirect association of Syk with TLR4 (61,74,75). In support of a direct association of Syk with TLR4, TLR4 contains a motif in the intracytoplasmic portion that is a putative Syk-SH2 domain recognition site, suggesting that Syk may associate with TLR4 directly through this domain (76).…”
Section: Sp600125 Does Not Inhibit Lps-induced Syk Phosphorylation-mentioning
confidence: 90%
“…The degree to which the deficiency of DAP12, FcR␥, or Syk directly affects ␣ V ␤ 3 integrin function in osteoclasts has not been fully explored. Syk-deficient neutrophils, macrophages, and platelets have been reported to show impaired signaling through integrins (14,24,25,28), and Syk can associate with the cytoplasmic domain of integrin ␤-chains (28). Supporting our hypothesis that ITAM signaling is linked to integrins, Faccio et al (9) recently reported that DAP12 Ϫ/Ϫ OCLs fail to migrate to osteopontin, an ␣ V ␤ 3 integrin ligand, whereas syk Ϫ/Ϫ OCLs fail to phosphorylate Pyk2 or Src on adherence to osteopontin.…”
Section: Discussionmentioning
confidence: 99%